A study on college students' perceived friendship with their teachers. - Elizaga, Maria Cristy M.
This study attempts to find out whether factors such as gender and year level affects one's having teacher-friends. Specifically, it seeks to answer the questions; Does being male or female affect one's having teacher-friends? Does being in the upper or lower year level affect one's having teacher-friends. The objectives of the study are: (1) to find out whether college students make friends with their teachers; (2) to find out the reasons why they make friends or why they do not make friends with their teachers; and (3) to find out whether gender and year level have a significant relationship with having teacher-friends., Since the distribution of the population is not equal, random sampling with proportional allocations by year level was used to draw out samples. The results were: 64 for the lowerclassmen and 36 for the upperclassmen greater percentage of college students who make friends with their teachers than those who do not. Among those who have teacher-friends, majority are females while minority are males, and majority are upper year level students whereas minority belong to the lower year level. Among those who do not have teacher-friends, minority are females while majority are males, and minority are upperclassmen whereas majority are lowerclassmen. The reasons why the respondents make friends with their teachers are as follows: (1) because teachers can help in their school works; and, (2) because they find their teachers friendly also. On the other hand, those who do not have teacher-friends explained that they feel uncomfortable in making friends with their teachers. Chi-square computations showed that there is a significant relationship between year level and having teacher-friends while there is no significant relationship between gender and having teacher-friends. It can be said that being male or female does not matter when a student tries to make friends with his or her teachers since what is considered important is that his or her teachers can help him or her in school work. Being an upperclassmen or lowerclassmen, on the other hand, greatly affects one's having teacher-friends since familiarity plays an important role in the development of friendship. Those in the upper year level, being already two years ahead of the lower year level students in school residence, are more familiar with the school teachers than those in the lower year level area. Familiarity, then, is closely associated with year level. (p)Therefore, male and female students, particularly those in the upper year level, have teacher-friends compared with those in the lower year level.